Perbandingan Efektivitas Biji Asam Jawa dan Biji Pepaya Sebagai Biokoagulan untuk Menurunkan BOD, COD, dan TSS pada Air Telaga - Rafi, Muhammad Ijlal; Mirwan, Mohamad (Jurnal Serambi Engineering, 2025)
Telaga Rambit in Gresik Regency, a water source for the local community, is currently polluted by domestic sewage. The coagulation-flocculation process is used to solve this problem. Chemical coagulants are often used in the coagulation-flocculation process, but chemical coagulants often produce sediment that is difficult to handle. Therefore, tamarind and papaya seeds were selected as natural coagulants due to their protein content which can act as polyelectrolytes. The aim of this research is to analyse the effect of pH and coagulant dosage in the coagulation-flocculation process and to compare the effectiveness of tamarind seeds and papaya seeds as biocoagulants in reducing BOD, COD and TSS. From the results of jar test analysis, papaya seed with a dose variation of 4000 mg/L and pH 7 is the best variation as it is able to reduce BOD up to 22.5%, COD 27.4% and TSS 51.22%. While tamarind seed at 2000 mg/L and pH 7 reduced BOD by 18.75%, COD by 23.4% and TSS by 46.3%. The results show that the two biocoagulants did not meet the quality standards in reducing BOD, COD and TSS in the lake water, so another combination process or use of other treatment alternatives is required.